f(

f(s(

R

↳Dependency Pair Analysis

F(x, c(y)) -> F(x, s(f(y,y)))

F(x, c(y)) -> F(y,y)

F(s(x), s(y)) -> F(x, s(c(s(y))))

Furthermore,

R

↳DPs

→DP Problem 1

↳Argument Filtering and Ordering

→DP Problem 2

↳AFS

**F(s( x), s(y)) -> F(x, s(c(s(y))))**

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

The following dependency pair can be strictly oriented:

F(s(x), s(y)) -> F(x, s(c(s(y))))

The following rules can be oriented:

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

Used ordering: Homeomorphic Embedding Order with EMB

resulting in one new DP problem.

Used Argument Filtering System:

F(x,_{1}x) ->_{2}x_{1}

s(x) -> s(_{1}x)_{1}

f(x,_{1}x) ->_{2}x_{1}

R

↳DPs

→DP Problem 1

↳AFS

→DP Problem 3

↳Dependency Graph

→DP Problem 2

↳AFS

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

Using the Dependency Graph resulted in no new DP problems.

R

↳DPs

→DP Problem 1

↳AFS

→DP Problem 2

↳Argument Filtering and Ordering

**F( x, c(y)) -> F(y, y)**

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

The following dependency pair can be strictly oriented:

F(x, c(y)) -> F(y,y)

The following rules can be oriented:

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

Used ordering: Homeomorphic Embedding Order with EMB

resulting in one new DP problem.

Used Argument Filtering System:

F(x,_{1}x) ->_{2}x_{2}

c(x) -> c(_{1}x)_{1}

f(x,_{1}x) ->_{2}x_{1}

s(x) -> s(_{1}x)_{1}

R

↳DPs

→DP Problem 1

↳AFS

→DP Problem 2

↳AFS

→DP Problem 4

↳Dependency Graph

f(x, c(y)) -> f(x, s(f(y,y)))

f(s(x), s(y)) -> f(x, s(c(s(y))))

Using the Dependency Graph resulted in no new DP problems.

Duration:

0:00 minutes